2016
DOI: 10.17116/jnevro2016116819-16
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive insight and dynamics of indicators of ultra-high risk for schizophrenia in young patients with non-psychotic forms of mental disorders

Abstract: Cognitive insight, although not linked to objective indicators of ultra-high risk for schizophrenia, predicts a decline in both total score of SOPS, and in the Positive symptoms subscale during the treatment of patients with personality disorders. In the groups with mood disorders and schizotypal disorder, cognitive insight reflects more anxiety and uncertainty related to patients' experience rather than the true conscious criticism. In the group with schizotypal disorder, it is also closely related to the sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 25 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…Five studies were eligible for our meta-analysis including 303 individuals with an ARMS status and 376 healthy controls (Clark, 2017;Kimhy et al, 2014;Ohmuro et al, 2018;Rasskazova et al, 2016;Uchida et al, 2014) (Table 1). All studies assessed insight abilities with a validated version of the BCIS (English (Clark, 2017;Kimhy et al, 2014), Japanese [Ohmuro et al, 2018;Uchida et al, 2014] and Russian [Rasskazova et al, 2016] languages). All participants were recruited from psychosis high-risk specialized clinics (ARMS) and from the community (controls).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Five studies were eligible for our meta-analysis including 303 individuals with an ARMS status and 376 healthy controls (Clark, 2017;Kimhy et al, 2014;Ohmuro et al, 2018;Rasskazova et al, 2016;Uchida et al, 2014) (Table 1). All studies assessed insight abilities with a validated version of the BCIS (English (Clark, 2017;Kimhy et al, 2014), Japanese [Ohmuro et al, 2018;Uchida et al, 2014] and Russian [Rasskazova et al, 2016] languages). All participants were recruited from psychosis high-risk specialized clinics (ARMS) and from the community (controls).…”
Section: Resultsmentioning
confidence: 99%
“…The Baujat plots indicated that the study of Rasskazova et al (2016) largely influenced all summary-ESg and contributed to their heterogeneity (Figure S1). In addition, this study demonstrated the highest risk of bias (QualSyst total = 10/22) as compared to the other studies included in the meta-analysis (QualSyst total = 18-to-20/22).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations